Determinants of Capital Structure: Internal Factors (Accounting) versus External Factors (Market) - Risal Rinofah; Diah Lestari Mumpuni (Sebelas Maret Business Review, 2019)
This study aims to examine the role of internal and external factors on the capital structure and specifically will test which factors are dominantly affecting the company's capital structure. The results of this test can be subject to additional discussion on the capital structure both in the classroom and academic space in general because so far, the discussion of factors affecting capital structure is still focused on internal factors of the company alone, especially in Indonesia. This goal will be achieved by observing manufacturing company panel data for 10 years (2006 - 2015). Data will be tested using multiple regression analysis techniques, both with the Common Effect (OLS), Fixed Effect or Random Effect Models. The three models are used to accommodate variations in the characteristics of the sample of companies studied which generally will affect the relationship between variables. The test results show that the best estimation model is Fixed Effect with the finding that the Capital Structure is determined by internal (Accounting) and external (Market) factors, which are negatively affected by Liquidity (Current Ratio), Company Age (Age), and Stock Market Value (Mispricing). This result also shows that companies in Indonesia adhere to the Market timing Hypothesis and Pecking Order Theory in determining the capital structure theory.